Evaluasi Faktor Pendorong Pelaksanaan Koordinasi Komunitas Pariwisata di Indonesia - Sari Lestari Zainal Ridho; Dewi Fadila; Fernando Africano; Hendra Sastrawinata; Muhammad Riska Maulana; Munparidi; Elvia Zahara; Ibnu Maja; Ummasyroh (FEB Universitas Sam Ratulangi Manado, 2023)
The purpose of this study is to evaluate whether the supporting factors influence the implementation of coordination in tourism communities or organizations in Indonesia. Data collection was carried out by survey through distribution of questionnaires to respondents who were samples from the entire population. The data were analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) technique. The results of the data processing show that the supporting factors in the form of common goals and government attention has significant positive influence the implementation of coordination in the tourism community. The results of this study have implications that it is important for every individual in an organization or community to focus on goals and it is important for stakeholders, namely the government to pay more attention.